THE ROLE OF STRATEGIC COST MANAGEMENT IN RATIONALIZING PRODUCT COSTS APPLIED RESEARCH IN THE GENERAL COMPANY FOR DAIRY PRODUCTS - Noor Fadhil Shahatha (Scholar Express Journals, 2022)
The target cost technique is one of the modern techniques that are used in determining the target selling price of products, as well as its role in rationalizing product costs through the correct use of available resources. Therefore, the research aims to clarify the role of the target cost technology in rationalizing the cost of the product and the research was based on the premise that the company’s application of the target cost technology leads to rationalizing the cost of the product and achieving competitive advantage. market and openness to each other
Keywords: Target Costing; Cost Rationalization